Stability and expression of K-ras mimotopes in freeze-dried recombinant Lactococcus lactis NZ3900-fermented milk powder during storage in vacuum packaging - How, Yu Hsuan; Teo, Michelle Yee Mun; In, Lionel Lian Aun; Yeo, Siok Koon; Bhandari, Bhesh; Yusof, Yus Aniza; Pui, Liew Phing (Oxford University Press, 2024)
Aims: This study aims to evaluate the storage stability of the freeze-dried recombinant Lactococcus lactis NZ3900-fermented milk powder expressing K-ras (Kristen rat sarcoma viral oncogene homolog) mimotopes targeting colorectal cancer in vacuum packaging. Methods and results: The freeze-dried L. lactis-fermented milk powder stored in 4-ply retortable polypropylene (RCPP)-polyamide (PA)-Aluminium (AL)-polyethylene terephthalate (PET) and aluminium polyethylene (ALPE) was evaluated throughout 49 days of accelerated storage (38°C and 90% relative humidity). The fermented milk powder stored in 4-ply packaging remained above 6 log10 CFU g-1 viability, displayed lower moisture content (6.1%), higher flowability (43° angle of repose), water solubility (62%), and survivability of L. lactis after simulated gastric and intestinal digestion (>82%) than ALPE packaging after 42 days of accelerated storage. K-ras mimotope expression was detected intracellularly and extracellularly in the freeze-dried L. lactis-fermented milk powder upon storage. Conclusions: This suggests that fermented milk powder is a suitable food carrier for this live oral vaccine.